Technology and Pedagogy: The Effect of Techno pedagogical Integration on Teacher Technostress in classroom Teaching - Jolly Chakrabortty; Dulumoni Goswami (urn:asian://2988-7534asian.v3i37)
The rapid integration of educational technology in classroom instruction has fundamentally transformed teaching practices while simultaneously introducing new psychological challenges for teachers, particularly technostress. This study aims to examine the relationship between teachers’ technostress and techno-pedagogical integration, identify key factors contributing to technology-induced stress, and analyze the role of professional development in mitigating or exacerbating this condition. Employing a qualitative-descriptive research design supported by a systematic analysis of empirical findings from classroom contexts, data were collected through document analysis and reflective synthesis of teachers’ experiences related to educational technology use. The data were analyzed thematically to capture recurring patterns of stress, pedagogical adaptation, and professional learning needs. The findings reveal that although educational technology enables innovative, flexible, and student-centered learning, it also generates significant stress stemming from technological complexity, information overload, limited instructional time, and the rapid pace of digital innovation. Furthermore, professional development emerges as a double-edged strategy: well-structured, needs-based, and institutionally supported programs effectively reduce technostress, whereas poorly designed or misaligned training intensifies teachers’ cognitive and emotional burden. The study concludes that sustainable techno-pedagogical integration requires coherent alignment between technology, pedagogy, and continuous professional learning. These findings contribute to the field of educational research by offering practical insights for policymakers and educational institutions in designing supportive digital learning environments, while future research is recommended to employ longitudinal and empirical approaches to further explore technostress dynamics across diverse educational settings.